Effect of A Fluoride Toothpaste Containing Enzymes and Salivary Proteins on Periodontal Pathogens in Subjects with Black Stain: A Pilot Study - Carelli, Maria; Zatochna, Iuliia; Sandri, Angela; Burlacchini, Gloria; Rosa, Angelica; Baccini, Francesca; Signoretto, Caterina (European Journal of Dentistry, 2023)
Objective Black stain (BS) is an extrinsic dental discoloration particularly difficult to treat. Although its etiology is not fully clear yet, chromogenic bacteria inside the oral cavity seem to be involved. In this pilot study, we evaluated whether a toothpaste containing enzymes and salivary proteins could improve oral health and reduce the presence of periodontal pathogens in subjects predisposed to BS discoloration.Materials and Methods Twenty-six subjects were enrolled in the study: 10 subjects without BS; 16 subjects with BS, randomly assigned in two groups: test (n = 8) and control (n = 8). The test group used a toothpaste containing sodium fluoride, enzymes, and salivary proteins. The control group used a toothpaste with amine fluoride. At enrollment and after 14 weeks, participants were subjected to professional oral hygiene, evaluation of BS (through Shourie index) and oral health status, collection of saliva and dental plaque samples. The presence of periodontal pathogens in plaque and saliva of all subjects was investigated by molecular analysis (PCR).Statistical Analysis The prevalence of investigated microbial species in patients with/without BS was performed by Chi-squared test. The variation in the prevalence of the investigated species after treatment in test and control group was analyzed by t-test.Results Clinical evaluation showed that 86% of participants with BS had a reduction in the Shourie index, independently from the toothpaste used. In particular, a greater reduction in the Shourie index was observed in subjects using an electric toothbrush. We did not observe an effect of the fluoride toothpaste containing enzymes and salivary proteins on the composition of the oral microbiota of the test subjects in comparison with controls. When comparing all subjects with BS (n = 16) and without BS (n = 10), P. gingivalis detection was significantly higher in saliva samples collected from subjects with BS (p = 0.0129).Conclusion We verified that the use of an enzyme-containing toothpaste alone is not sufficient to prevent the formation of BS dental pigmentation in subjects predisposed to this discoloration. Mechanical cleaning, especially using electrical toothbrushes, seems to be useful to counteract BS formation. Moreover, our results suggest a possible association between BS and the presence of P. gingivalis at the salivary level.
Keywords: black stain; enzyme-based toothpaste; oral hygiene; periodontal pathogens.